IoT-based river water quality monitoring - Soheil Fakheri; Nenad Komazec; Hashem Saberi Najafi (Computational Algorithms and Numerical Dimensions)
This paper, named IoT-based river water quality monitoring, gives the outcome of quality river water with the advantage of various advanced techniques, the Internet of Things, and Wireless Sensor Networks (WSNs). As part of this, we have made the things to collect the data and transfer the data to the software that we have made. Then, the data we collect using various equipment will be analyzed using the software we have designed. Besides that, we automate the monitoring process with the system's hardware, data visualization, and software. This water quality monitoring system has been a significant issue and can be used digitally, intelligently, and effectively to improve river water quality.